The Essential Involvement of the Omentum in the Peritoneal Defensive Mechanisms During Intra-Abdominal Sepsis - Liu, Ying; Hu, Jian-nan; Luo, Ning; Zhao, Jie; Liu, Shu-chang; Ma, Tao; Yao, Yong-ming (Frontiers in Immunology, 2021)
Although the capability of the omentum to resolve inflammation and fight bacteria has been appreciated for many decades, the underlying mechanisms remain mostly unknown. Here, we demonstrate that there is a significant increase in mortality in mice subjected to omentectomy and cecal ligation and puncture (CLP) in comparison with CLP alone, which was correlated with impairment in intraperitoneal bacterial clearance together with an increase in proinflammatory cytokines expression. Notably, in response to peritoneal infections, both the number and the size of the milky spots (MSs) in the omentum increased tremendously and they also support innate-like B1 cell responses and local IgM production in the peritoneal cavity. Furthermore, not only the migration but also the functional activities of neutrophils were diminished in the absence of the omentum. These data collectively show that the omentum contributes more to peritoneal immune responses during septic peritonitis than has been heretofore recognized. Harnessing the function of omentum harboring MSs to increase its protective effectiveness might have important biological and therapeutic implications for the control of intra-abdominal infections.